Aflatoxins: Finding Solutions for Improved Food Safety by Sheryl Schneider - Schneider, Sheryl (2013)
IFPRI Policy Seminar "Aflatoxins: Finding Solutions for Improved Food Safety" held at IFPRI on November 5, 2013. Presentation by Sheryl Schneider, World Food Programme.